Государственная служба России: учеб. пособие / Д.Н. Бахрах - Бахрах Демьян Николаевич (Проспект, 2009)
Экземпляры: СЭ (20090603) / Инвентарный номер: 1075915 / Цена: / Сис.шифр: 67.401 / Авт.знак: Б 30 / ГРНТИ: 10 / ББК: 67.401.02